Quantitatively relating multinucleon transfer and fusion - K.J. Cook; E.C. Simpson; D.C. Rafferty; D.J. Hinde; M. Dasgupta; J. Buete; S.L. Hayles; L. Corradi; M. Evers; E. Fioretto; D.H. Luong; T. Mijatović; et al. (Physics Letters B)
Above-barrier capture cross-sections for heavy ion-fusion are systematically lower than predictions, with the discrepancy rapidly growing with increasing charge product of the colliding nuclei. It has been proposed that this can be explained by the onset of energy dissipation outside the barrier. Here, we present measurements of both capture cross-sections and the reflected flux in the 32S+208Pb reaction to quantitatively correlate signatures of energy dissipation with the reduction of capture. The measurements of the reflected flux show that multinucleon transfer begins outside the barrier leading to high excitation energies and effective energy dissipation. We deduce the resulting change in kinetic energy relative to the new potential, and combine these with coupled channels calculations. This demonstrates that discrepancies between calculations and experimental cross-sections and barrier distributions can be quantitatively related to the observed multinucleon transfer.